London voices, London lives : tales from a working capital - Hall, Peter, 1932-2014 (Policy Press, 2007)
Alongside the current media public preoccupation with high risk offenders, there has been a shift towards a greater focus on risk and public protection in UK criminal justice policy. This report draws together a distinguished panel to critically consider both the theory and application of the risk concept in work with young people and young adults that offend, both in terms of public protection and of young people's own vulnerability to being harmed.